Mean Adiponectin Levels and Frequency of Hypoadiponectinemia in Gestational Diabetes Mellitus - Saba Raza; Usman Ali; Adnan Mustafa Zubairi; Erum Salim (ziauddin University, 2024)
Background: Insulin resistance, a major pathogenic factor in Gestational Diabetes Mellitus (GDM), has an inverse correlation with adiponectin; therefore, the role of adiponectin in the pathogenesis of GDM has been suggested. The study aimed to determine mean adiponectin levels and the frequency of hypoadiponectinemia in patients with GDM. Methods: The study was carried out at Dr. Ziauddin University Hospital, Karachi from June 2016 to December 2017. A total of 99 women of age group 15-45 years diagnosed with GDM on Oral Glucose Tolerance Test (OGTT) at 24-28 weeks of gestations were included in the study. Patient's data was recorded on proposed proforma, regarding age, gestational age, parity, ethnicity, Body Mass Index (BMI). Serum samples for quantitative estimation of Adiponectin were collected. OGTT and were analyzed on Immunoassay in conjunction with control materials. Mean±Std. was calculated for quantitative variables percentages and frequencies for categorical variables. For significant differences between categories, an independent t-test and Chi-square test were used. Results: High frequency of hypoadiponectinemia was observed in GDM women with mean adiponectin levels of 6.90±2.86 µg/ml (95%CI: 6.33 to 7.47). Out of 99 GDM women, 91(91.92%) had hypoadiponectinemia while 8(8.08%) had normal Adiponectin levels. A significant (p=0.05) association was found between BMI and hypoadiponectinemia. Conclusion: In the majority of GDM females, hypoadiponectinemia was observed. The high frequency of hypoadiponectinemia suggests further large-scale studies, are warranted to ascertain the diagnostic accuracy of adiponectin as a potential biomarker for GDM. Keywords: Gestational Diabetes; Adiponectin; Pregnancy; Glucose Intolerance.